Comparison of Frictional Resistance Among Conventional, Active and Passive Self-Ligating Brackets with Different Combinations of Arch Wires: A Finite Elements Study (2016)
ABSTRACT: The aim of this study was to compare frictional resistance among conventional, passive and active selfligating brackets using Finite Elements Analysis (FEA). Seventynine (79) slide tests were performed by combining an upper first bicuspid conventional bracket, 0.018” stainless steel wires and 0.010” ligature by means of an INSTRON 3345 load system to obtain average maximum static frictional resistance (MSFR). This value was compared to the FR (frictional resistance) obtained by simulation of a slide of the same combination by FEA following conventional bracket modeling by means of Computer Aided Design (CAD). Once the FEA was validated, bracket CADs were designed (upper right first bicuspid conventional, active and passive selfligating bracket) and bracket properties calculated. MSFR was compared among conventional, active and passive selfligating brackets with different alloys and archwire cross sections such as 0.018”, 0.019” x 0.025”and 0.020” x 0.020”. Passive selfligating brackets had the lowest MSFR, followed by conventional brackets and active selfligating brackets. In conventional brackets, a 0.018” archwire produced a linear pattern of stress with maximum concentration at the center. Conversely, stress in 0.020 x 0.020” and 0.019 x 0.025” archwires was distributed across the width of the slot. The highest normal forces were 1.53 N for the 0.018” archwire, 4.85 N for the 0.020 x 0.020” archwire and 8.18 N for the 0.019 x 0.025” archwire. Passive selfligating brackets presented less frictional resistance than conventional and active selfligating brackets. Regardless of bracket type, greater contact area between the slot and the archwire and the spring clip increased frictional resistance.